2023
DOI: 10.1111/eip.13436
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive health treatment priorities and preferences among young people with mental illness: The your mind, your choice survey

Abstract: AimCognitive impairments negatively impact the everyday functioning of young people with mental illness. However, no previous study has asked young people (1) how much of a priority cognitive functioning is within mental health treatment, and (2) what types of cognition‐focused treatments are most appealing. The current study aimed to address these questions.MethodsYour Mind, Your Choice was a survey‐based study involving an Australian sample of young people who were receiving mental health treatment. The surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…Qualitative research has shown that current approaches in treating cognition in mental health services typically default to a ‘deficit-based’ approach to make up for a ‘loss’ (e.g. focuses on remediation of deficits), even though clinicians and young people with mental illness view strengths-based approaches favourably (Bryce et al, 2023; Steele et al, 2021). Considering the impact of being identified as ‘cognitively impaired’ is important too, with this label having been described as a ‘self-fulfilling prophecy’ which is taken on as an ‘identity in a very profound way’ (Jones, 2023).…”
Section: Using Cognitive Strengths In Cognitive Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research has shown that current approaches in treating cognition in mental health services typically default to a ‘deficit-based’ approach to make up for a ‘loss’ (e.g. focuses on remediation of deficits), even though clinicians and young people with mental illness view strengths-based approaches favourably (Bryce et al, 2023; Steele et al, 2021). Considering the impact of being identified as ‘cognitively impaired’ is important too, with this label having been described as a ‘self-fulfilling prophecy’ which is taken on as an ‘identity in a very profound way’ (Jones, 2023).…”
Section: Using Cognitive Strengths In Cognitive Interventionsmentioning
confidence: 99%
“…Research supports this discrepancy between objective and subjective cognitive impairment. In young people with mental illness, very high rates (70%) of subjective cognitive difficulties have been reported, but a much lower rate (31%) have reported receiving treatment targeting cognition (Bryce et al, 2023). While this may reflect other systemic factors in mental health provision, this low rate of cognitive intervention for individuals reporting significant cognitive difficulties may relate to clinicians typically only delivering interventions targeting cognition when objective cognitive impairment is present.…”
Section: Relating Cognitive Impairment and Strength To Life Functioningmentioning
confidence: 99%
“…Our recent work also shows that such early intervention for cognition is also aligned with the preferences of young people. Cognition is a high treatment priority for young people with mental illness, alongside the treatment of mental health symptoms (Bryce et al, 2023).…”
mentioning
confidence: 99%
“…In our 'Your Mind, Your Choice' survey (Bryce et al, 2023), we asked young people who had recently received mental health treatment to rate the importance of 20 different recovery domains. Respondents were 243 young people (mean age = 20.07, S.D.…”
mentioning
confidence: 99%
See 1 more Smart Citation